Need for bioethics in higher education - Bermúdez de Caicedo, Clemencia (Acta Bioethica, 2006)
Higher education should include training in values, in order to generate a culture of respect for life, thus influencing positively human beings' actions. It's imperative to review the curriculum -real and concealed- to identify what will really allow us to train not only successful professionals, but citizens involved in social development.